Anti-inflammatory celastrol promotes a switch from leukotriene biosynthesis to formation of specialized pro-resolving lipid mediators. (May 2021) - Pace, Simona; Zhang, Kehong; Jordan, Paul M.; Bilancia, Rossella; Wang, Wenfei; Börner, Friedemann; Hofstetter, Robert K.; Potenza, Marianna; Kretzer, Christian; Gerstmeier, Jana; Fischer, Dagmar; Lorkowski, Stefan; et al.
Abstract: The pentacyclic triterpenoid quinone methide celastrol (CS) from Tripterygium wilfordii Hook. F. effectively ameliorates inflammation with potential as therapeutics for inflammatory diseases. However, the molecular mechanisms underlying the anti-inflammatory and inflammation-resolving features of CS are incompletely understood. Here we demonstrate that CS potently inhibits the activity of human 5-lipoxygenase (5-LOX), the key enzyme in pro-inflammatory leukotriene (LT) formation, in cell-free assays with IC50 = 0.19–0.49 µM. Employing metabololipidomics using ultra-performance liquid chromatography coupled to tandem mass spectrometry in activated human polymorphonuclear leukocytes or M1 macrophages we found that CS (1 µM) potently suppresses 5-LOX-derived products without impairing the formation of lipid mediators (LM) formed by 12-/15-LOXs as well as fatty acid substrate release. Intriguingly, CS induced the generation of 12-/15-LOX-derived LM including the specialized pro-resolving mediator (SPM) resolvin D5 in human M2 macrophages. Finally, intraperitoneal pre-treatment of mice with 10 mg/kg CS strongly impaired zymosan-induced LT formation and simultaneously elevated the levels of SPM and related 12-/15-LOX-derived LM in peritoneal exudates, spleen and plasma in vivo. Conclusively, CS promotes a switch from LT biosynthesis to formation of SPM which may underlie the anti-inflammatory and inflammation-resolving effects of CS, representing an interesting pharmacological strategy for intervention with inflammatory disorders. Graphical Abstract: ga1 Highlights: 5-LOX is a high affinity target for celastrol (CS) with IC50 of 0.19–0.49 µM. CS blocks 5-LOX-derived leukotriene formation in PMNL and M1 macrophages. in M2 macrophages CS elicits specialized pro-resolving mediator (SPM) formation. CS impairs the levels of leukotrienes but elevates SPM in murine peritonitis.